PENGARUH STRATEGI PEMBELAJARAN EXPLICIT INSTRUCTION TERHADAP HASIL BELAJAR SISWA KELAS XI PADA MATA PELAJARAN 2 DIMENSI JURUSAN MULTIMEDIA SMKN 2 PADANG PANJANG - melda yanti (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2022)
The low quality of student learning outcomes is influenced by the strategy delivered by the teacher that is not appropriate so that it has a major impact on student learning outcomes that are not optimal. For this reason, it is important that there is a breakthrough in the form of a strategy implemented by a teacher. The objectives of this research are; 1) To find out the learning outcomes of class XI students before and after the implementation of the Explicit Instruction Learning Model in the 2-dimensional subjects of the Multimedia Department at SMKN 2 Padang Panjang, 2) To determine the effect of the implementation of the Explicit Instruction Learning Model on student learning outcomes. The research method uses a quantitative approach. The data analysis technique used in this research is a quantitative research technique. By converting the scores into scores and using a t-test (paired sample test). The results in this study are explicit instructional learning strategies have a significant effect on student learning outcomes in class XI in the 2 Dimensional Subject of the Multimedia Department of SMKN 2 Padang Panjang. The application of the learning model with the explicit instruction strategy in the 2 Dimensional Subject of the Multimedia Department in the experimental class went well.